2014
DOI: 10.3174/ajnr.a3850
|View full text |Cite
|
Sign up to set email alerts
|

Association between Resting-State Coactivation in the Parieto-Frontal Network and Intelligence during Late Childhood and Adolescence

Abstract: BACKGROUND AND PURPOSE:A number of studies have associated the adult intelligence quotient with the structure and function of the bilateral parieto-frontal networks, whereas the relationship between intelligence quotient and parieto-frontal network function has been found to be relatively weak in early childhood. Because both human intelligence and brain function undergo protracted development into adulthood, the purpose of the present study was to provide a better understanding of the development of the parie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“… Langeslag and colleagues (2013) found a significant positive correlation between IQ and connectivity in the right PFC and pPC in a sample of 6–8 year olds. Li and Tian (2014) examined the relationship between the right and left frontoparietal control networks and IQ in childhood and adolescence: they also found that connectivity strength in regions of the right network were positively associated with IQ. Other research also suggests that the relation between IQ and connectivity in the CEN or frontoparietal networks persists into adulthood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Langeslag and colleagues (2013) found a significant positive correlation between IQ and connectivity in the right PFC and pPC in a sample of 6–8 year olds. Li and Tian (2014) examined the relationship between the right and left frontoparietal control networks and IQ in childhood and adolescence: they also found that connectivity strength in regions of the right network were positively associated with IQ. Other research also suggests that the relation between IQ and connectivity in the CEN or frontoparietal networks persists into adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that activity in the CEN, but not the salience network, correlated with performance on executive control tasks. Emerging evidence suggests the strength of within-network connectivity in the CEN, (also called the frontoparietal control system/network; Vincent et al, 2008 ) is associated with higher IQ in children, adolescents, and adults (e.g., Langeslag et al, 2013 , Li and Tian, 2014 , Song et al, 2008 ). CEN activity has been shown to be anticorrelated with activity in the DMN in healthy adults ( Fox et al, 2005b , Menon and Uddin, 2010 , Sridharan et al, 2008 ), and it has been proposed that it may even directly inhibit DMN activity under certain circumstances ( Chen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike high school students, college students did not show a decrease in activity in regions of the dmPFC and lPFC that overlap with the CEN (Sherman et al., ). The CEN is frequently activated during tasks involving executive function, including response inhibition and cognitive control, and metrics of CEN connectivity have been found to relate executive function and IQ in youth and adults (e.g., Li & Tian, ; Seeley et al., ). In other words, high school but not college students showed decreased activity in frontal cognitive control regions when viewing images of risky behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Of greatest relevance to the present review, a study focusing on the neurodevelopment of second-order relational reasoning recently showed that frontoparietal connections strengthened with age, and were more tightly coupled than shorter-range frontoinsular connections for second- relative to first-order relational problems (Bazargani et al, 2014). More broadly, various studies have shown that tighter resting-state functional connectivity among LFPN regions is associated with better relational reasoning, as measured by nonverbal IQ scores (Langeslag et al, 2013) or full-scale IQ scores (Song et al, 2008; Li and Tian, 2014). Taken together, these studies suggest that tighter coupling within the LFPN is associated with better cognitive performance on various tasks, including relational reasoning.…”
Section: Lfpn Functional Connectivitymentioning
confidence: 99%